Exhuming Labor: Alienation and Rural Affiliation in Spanish Migrant Poetry - Carlos Varón González (Studies in 20th & 21st Century Literature, 2020)
One of the consequences of the 2008 financial crisis was that many young college graduates from the Spanish state left the country, faced with unemployment rates over 40% at home. Whereas Spanish economic growth before the crisis had pushed the narrative that a young generation was predisposed to transnational circulation, the experience of migration challenged the identification of large transnational cities as sites of emancipatory modernization. Fruela Instead, Fruela Fernández’s Una paz europea (A European Peace) and Lara Dopazo Ruibal’s ovella (sheep) point to them as the background to vulnerable, animalized, racialized, alienated bodies. The transnational city is not the promised locale of worldly curiosity and growth but a space of alienation. Relying on the work on emotions of Sara Ahmed, Eva Illouz, and Laurent Berlant, this essay shows how the emotional numbness of the alienated migrant worker is not just the byproduct of neoliberal labor, but a change in the orientation and the self-understanding of modern Spanish culture. Fernández and Dopazo’s book are affiliative acts aiming at locating an alternative modernity in modes of production contrary to global capitalism. The country is not nostalgic or the restoration of an idyllic scenario, but an attempt to imagine otherwise our social space.
Keywords: alienation; Fruela Fernández; Lara Dopazo Ruibal; poetry; migration